From personality types to social labels: the impact of using MBTI on social anxiety among Chinese youth - Wu, Wenjing; Hao, Wenzhu; Zeng, Gao; Du, Weiyi (Frontiers in Psychology, 2024)
With an increasing popularity among Chinese youth, the Myers-Briggs Type Indicator (MBTI) has gradually evolved from a personality label to a social label. This study primarily explores the impact of using MBTI on social anxiety among Chinese youth. Through a questionnaire survey, we collected data from 247 males and 222 females and conducted quantitative analysis using the SPSS software and the Process macro plugin. The study found no strong correlation between the use of MBTI as a social label and social anxiety. Further, the study introduced ego identity, belonging, and impression management as mediating variables and discovered that under the mediating effects of ego identity and impression management, the use of MBTI has a significant impact on social anxiety. The research reveals the complex role of MBTI in the social interactions among Chinese youth and provides a new perspective for understanding the impact of online social labels on the mental health of youth groups. Of course, the study also has limitations in sample size and inadequate control of variables. Future research should expand the sample size and introduce more potential influencing factors to further verify and expand the existing conclusions.